ANÁLISIS DE LA POBREZA DESDE UN ENFOQUE MULTIDIMENSIONAL EN EL DEPARTAMENTO DE CÓRDOBA PARA EL AÑO 2012 (2016)
This paper provides a measurement study of poverty in different dimensions in the department of Córdoba for 2012 using the Multidimensional Poverty Index (PMI) information from the Survey of Quality of Life. Population was characterized taking into account the dimensions and variables proposed by the PMI and then the different multidimensional poverty indicators were found. The results show that education, employment and housing conditions are the critical variables within the department in the period studied, identifying needs and opportunities for access to education, conditions which ensure the permanence of students in each grade, generation of quality employment in order to reduce informality and the improvement of housing conditions in the community.